Analysis of electromagnetic transitions in 176,178Hf - Usmanov, Phazlitdin; Okhunov, Abdurahim; Salikhbaev, Umar; Vdovin, Aleksey (SP MAIK Nauka/Interperiodica, 2010)
The structure of excited states and nonadiabatic effects manifested in the energies and probabili ties of electromagnetic transitions are studied in the context of a phenomenological model taking into account the Coriolis mixing of the lowlying states of positive parity in rotational bands. Energies and the structure of wave functions of excited states are calculated. The calculated energies are in agreement with experimental data. The mixing effect is demonstrated to play an important role in the wave functions of vibra tional states. The probabilities of E2 and M1 transitions are calculated. The theoretical values of ratios and multipolemixing coefficients δ(E2/M1) of transitions from the first and second β and γ vibrational bands are compared with the available experimental data.